POLITICAL PHILOSOPHY OF WILLIAM OF OCKHAM - Trush, T. (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2018)
The purpose article will deal with the works by William of Ockham, an English scholastic philosopher Franciscan. Interconnection of the thinker’s philosophical views with his political judgments is highlighted. The tasks and duties of the Church and the state are defined. The results of this study have been developed and introduced into the educational process of the Taras Shevchenko National University of Kyiv. This is a discipline "History of Philosophy" in "Political Science". The results of the article give an opportunity to broaden and deepen theoretical knowledge of students in the field of historical and philosophical science of the Middle Ages. This article deals directly with William of Ockham’s political thought. The influence of Ockham’s philosophical opinions on political views is also shown. The political illness of papacy plenitude potestatis and the possibilities of solving it is clarified. As Okkama’s authorial position in solving political issues is far from perfect, the article shows the progress in solving Marsilius of Padua’s political issues. The obtained results allow stating that such studies give a possibility to deepen the theoretical knowledge of the students "political science" and "public service" at the Taras Shevchenko National University of Kyiv.